Dual-layer detector CT of the head: Initial experience in visualization of intracranial hemorrhage and hypodense brain lesions using virtual monoenergetic images. Issue 108 (November 2018) - Lennartz, Simon; Laukamp, Kai Roman; Neuhaus, Victor; Große Hokamp, Nils; Le Blanc, Markus; Maus, Volker; Kabbasch, Christoph; Mpotsaris, Anastasios; Maintz, David; Borggrefe, Jan
Abstract: Purpose: Retrospective comparison of diagnostic quality of virtual monoenergetic images (VMI) and conventional images (CI) reconstructed from dual-layer detector CT (DLCT) regarding intraparenchymal hemorrhage (IPH) and hypodense parenchymal lesions (HPL) of the brain. Methods: 58 patients underwent unenhanced DLCT of the head. CI and VMI ranging from 40 to 120 keV were reconstructed. Objective image quality was assessed using ROI-based measurements within IPH, HPL, grey matter, white matter and cerebrospinal fluid, from which contrast to noise ratio (CNR) was calculated. Two radiologists assessed IPH, HPL, artifacts and image noise on a 5-point Likert-scale. Statistical significance was determined using Wilcoxon rank sum test. Results: In comparison to conventional images, CNR of HPL to white matter was significantly increased in VMI at 120 keV (p ≤ 0.01), whereas at 40 keV, CNR to grey matter was enhanced (p ≤ 0.0001). Contrary, CNR of IPH to white matter was increased at 40 keV (p ≤ 0.01), while CNR to grey matter was improved at 120 keV (p ≤ 0.01). Subjective readings confirmed best delineation of IPH within grey matter at 120 keV. Both readers detected four additional hyperdense lesions within white and one within grey matter at 40 keV. Conclusions: VMI obtained with DLCT can improve depiction of hypodense parenchymal lesions and intraparenchymal hemorrhage. The initial data show a great dependency on the type of pathology and on its location: hypodense lesions in white matter and hyperdense lesions in grey matter are better visualized in higher keV reconstructions, while hyperdense lesion in white matter and hypodense lesions in grey matter are better visualized at low keV values.